Abnormal Rich Club Organization of Structural Network as a Neuroimaging Feature in Relation With the Severity of Primary Insomnia - Wu, Yunfan; Zhou, Zhihua; Fu, Shishun; Zeng, Shaoqing; Ma, Xiaofen; Fang, Jin; Yang, Ning; Li, Chao; Yin, Yi; Hua, Kelei; Liu, Mengchen; Li, Guomin; et al. (Frontiers in Psychiatry, 2020)
Purpose: Insomnia is the most prevalent sleep complaint in the general population but is often intractable due to uncertainty regarding the underlying pathomechanisms. Sleep is regulated by a network of neural structures interconnected with the core nodes of the brain connectome referred to as the ‘rich club’. We examined alterations in brain rich-club organization as revealed by diffusion tensor imaging (DTI) and the statistical relationships between abnormalities in rich-club metrics and the clinical features of primary insomnia (PI). Methods This study recruited 43 PI patients and 42 age-, sex- and education level-matched healthy controls. Differences in global and regional network parameters between PI and HC groups were compared by nonparametric tests, and Spearman’s correlations were calculated to assess associations of these network metrics with PI-related clinical features, including disease duration and scores on the Pittsburgh Sleep Quality Index, Insomnia Severity Index, Self-Rating Anxiety Scale and Self-Rating Depression Scale. Results Weighted white matter networks exhibited weaker rich-club organization in PI patients than healthy controls across different thresholds (50%, 75% and 90%) and parcellation schemes (AAL-90 and AAL-1024). Aberrant rich-club organization was found mainly in limbic-cortical-basal ganglia circuits and the default-mode network. Conclusions Abnormal rich-club metrics are a characteristic feature of PI-related to disease severity. These metrics provide potential clues to PI pathogenesis and may be useful as diagnostic markers and for assessment of treatment response.